Sustainable Ecological Development of the Global Economic System. The Institutional Aspect - DOVGAL, Olena; GONCHARENKO, Nataliia; RESHETNYAK, Olena; DOVGAL, Georgiy; DANKO, Natalia; SHUBA, Tetiana (Journal of Environmental Management and Tourism; Vol 11 No 3 (2020): JEMT Volume XI Issue 3(43) Summer 2020DO - 10.14505//jemt.v11.3(43).27, 2020)
Socio-ecological-economic relations and the institutional environment are shaped and changed in complex interaction. The main aim of this research is an institutional format development of the interaction of economic, social and environmental components of the global economic system, which could regulate the impact of institutional mechanisms and instruments of implementing the principles of ecological growth on the global economic system, for ensuring sustainable ecological development of the world economy. The methodological basis of the article is the general scientific methods of scientific research: induction and deduction, comparative analysis and synthesis, generalization and realization of results, as well as historical and methods of logical analysis and abstract modeling.  The article summarizes the main findings obtained from the study of the institutional aspect of ensuring sustainable ecological development of the global economic system. The search for strategic priorities for the development of global economic systems has necessitated considering the need for complex institutional changes, which should contribute to ensuring socio-economic growth in the context of limited natural resources and the need to solve global environmental problems. In present research the authors have systematized and analyzed institutional instruments required for regulating ecological and economic relations and institutional leverage for increasing the appeal of environmental protection measures. The authors have proposed an institutional format for the interaction of economic, social and environmental components of the global economic system, which is the basis for policy development towards creating and developing a system of environmentally sensitive administration and management in the framework of green global economic development.